2021
DOI: 10.2174/1573405617666210215142528
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Quantitative Assessment of COVID-19 Pneumonia on Chest CT: The Relationship with Disease Severity and Clinical Findings

Abstract: Background: Lungs are the primary organ of involvement of COVID-19, and the severity of pneumonia in COVID-19 patients is an important cause of morbidity and mortality. Aim: We aimed to evaluate the visual and quantitative pneumonia severity on chest computed tomography (CT) in patients with coronavirus disease 2019 (COVID-19) and compare the CT findings with clinical and laboratory findings. Methods: We retrospectively evaluated adult COVID-19 patients who underwent chest CT, clinical scores, laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…In total, 21 studies were included in the analysis 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 .…”
Section: Resultsmentioning
confidence: 99%
“…In total, 21 studies were included in the analysis 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 .…”
Section: Resultsmentioning
confidence: 99%
“…In semiquantitative evaluation, each lung lobe’s involvement percentage is calculated visually, and the pneumonia severity score of the whole lung is determined by summing up the involvement rates. 5 , 46 Quantitative CT evaluation is a method that provides an objective and rapid assessment of COVID-19 pneumonia extent and predicts patient prognosis 47 - 49 ( Figure 3 ). Ufuk et al 46 demonstrated that pneumonia severity was an independent predictor of prolonged hospitalization (adjusted odds ratio [OR]: 1.20, P < .001), intubation (OR: 1.73, P < .001), and death (OR: 2.13, P = .026).…”
Section: Imaging Findings Of Covid-19 Pneumoniamentioning
confidence: 99%
“…Ufuk et al 46 demonstrated that pneumonia severity was an independent predictor of prolonged hospitalization (adjusted odds ratio [OR]: 1.20, P < .001), intubation (OR: 1.73, P < .001), and death (OR: 2.13, P = .026). Kaya et al 47 reported that quantitative CT assessment had high sensitivity and specificity in distinguishing disease severity and predicting prolonged hospitalization. Salvatore et al 50 reported that an overall pneumonia severity score of ≥50% indicates a poor prognosis.…”
Section: Imaging Findings Of Covid-19 Pneumoniamentioning
confidence: 99%
“…Computed tomography (CT) is an essential diagnostic criterion as well as for follow-up of the disease, especially in RT-PCR negative patients, who typically present a bilateral groundglass view in lower zones with multiple foci and peripheral or subpleural patch-like consolidation areas [3][4][5].…”
Section: Introductionmentioning
confidence: 99%